Actividad antibiótica de las fracciones del extracto crudo de Rapidithrix thailandica s80 de playa Laguna Grande – Paracas - Capuñay Reyes, Patricia Pamela (2019)
The objective of this study was to evaluate the antibiotic activity of the fractions of the crude extract of Rapidithrix thailandica s80 from Laguna Grande beach - Paracas. The bacterium was grown in liquid medium using marine broth, acetone was used as extraction solvent. The extract was concentrated under reduced pressure to dryness. Then a chromatographic fractionation was performed using Sephadex LH-20 as a stationary phase and methanol as the mobile phase. Three fractions were collected according to the presented color (light green, dark green and beisch). For the antibiotic activity, a concentration of 20 mg/mL was prepared, determined by the disk agar diffusion method and compared to methicillin-resistant Staphylococcus aureus (MRSA) ATCC 43300, Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Bacillus subtilis ATCC 6633 and Pseudomonas aeruginosa. The minimum inhibitory concentration (MIC) was determined by microdilution and the minimum bactericidal concentration (MBC), in Mueller Hinton broth and agar, respectively. It was observed that fraction 3 showed greater inhibition halo (13 mm) against ATCC 43300 MRSA and S. aureus ATCC 25923, unlike fraction 2 that had a lower inhibition halo (11 mm) and fraction 1 that did not present halo against pathogens. Fraction 3 also presented a MIC and MBC of 0.13 mg / mL. It is concluded that fraction 3 of the acetone extract showed higher bactericidal activity against ATCC 43300 and S. aureus ATCC 25923 MRSA. We also determined the R of fraction 3 that presented 2 spots (0.78, 0.85).